Indonesia’s Digital Financial and Economic Transformation Through Digitalize Redenomination - Silvia Puspa Kumaeroh; Muhammad Ayesha Arif Sandy; Muhammad Ikhwanurrohiim Septenta; Fina Dwi Utami; Mutiara Tresna Parasetya (International Journal of Science and Applied Science: Conference Series, 2021)
The financial sector plays an important role in the economy and continues to develop. Some central banks are actively exploring the initiation of digital currency that will become a legal tender [6]. This digital currency is known as the Central Bank Digital Currency (CBDC). Apart from the technological aspect, the CBDC must also be supported by the efficient value of the rupiah denomination. Therefore, it is necessary to simplify the number of digits in the rupiah denomination with a redenomination policy. The implementation of the two policies separately will take a long time in the formulation process. This research comes up with a new concept called "Digitalize Redenomination". This concept that has never existed in previous studies integrates both redenomination policy and CBDC at the same time. The research methods are both qualitative and quantitative. The qualitative method is done by analyzing literature study data and interviews with Bank Indonesia and economists. While the quantitative method is done by analyzing questionnaire data of the public. From this research, it is concluded that the current condition of the financial system in Indonesia has entered the era of digital transformation and at the same time, Indonesia also needs to simplify the rupiah denomination. The Digitalize Redenomination mechanism has the potential to be applied in Indonesia. However, the application of this concept cannot be implemented until the national economic condition is stable. After the economy is stable, the government can review this concept to be implemented in Indonesia.